Experimental kinetic study of the reactions between OH radicals and three 2‐butenes over the temperature range 220–370 K and pressure range 0.67–40 kPa (5–300 Torr). Issue 5 (24th January 2023) - Orkin, Vladimir L.; Khamaganov, Victor G.; Kurylo, Michael J.
Abstract: Gas phase reactions between OH radicals and three 2‐Butenes were studied using a flash photolysis resonance‐fluorescence technique over the temperature range 220–370 K and total gas pressures of 0.67 kPa (5 Torr) to 40 kPa (300 Torr). Measured rate constants exhibited weak negative temperature dependences. Most studies were carried out in argon, but some test experiments employed helium or nitrogen as the bath gas. Rate constants of OH reactions with cis‐ 2‐butene and trans‐ 2‐butene were found to exhibit a pressure dependence at room temperature and above. Kinetic parameters k 0 ( T ) k_0(T) and k ∞ ( T ) k_∞ (T) describing termolecular rate constants in Ar bath gas were derived for both reactions and can be used to calculate rate constants at the Earth's atmospheric conditions. The high‐pressure limiting rate constants are k ∞ Z ( T ) = 5.78 × 10 − 11 × ( 298 T ) 1.51 k_∞ ^Z(T) = 5.78 × 10^ - 11 × ( 298T )^1.51, cm 3 molecule −1 s −1 and k ∞ E ( T ) = 6.59 × 10 − 11 × ( 298 T ) 1.54 k_∞^E(T)=6.59×10^-11×(298T)^1.54, cm 3 molecule −1 s −1 for OH addition reactions with cis‐ 2‐butene and trans‐ 2‐butene, respectively. Their rate constants at 1 atm (760 Torr, 101 kPa) pressure can be represented as kZ ( T, 1 atm ) = 5.93 × 10 −11 × ( T /298) −1.61 × exp ( − 17/ T ), cm 3 molecule −1 s −1 and kE ( T, 1 atm ) = 6.75 × 10 −11 × ( T /298) −1.64 × exp ( − 16/ T ), cm 3 molecule −1 s −1 . The rate constant of the OH addition reaction with 2, 3‐dimethyl‐2‐butene was found to be pressure independent under our conditions and can be represented as kTME ( T ) = 14.08 × 10 −11 × ( T /298) −1.714 × exp ( − 95.7/ T ), cm 3 molecule −1 s −1 with k TME (298 K) = (10.21 ± 0.30) × 10 −11, cm 3 molecule −1 s −1 . Complementary measurements of IR absorption spectra of cis‐ 2‐butene and trans‐ 2‐butene were done between 500 and 3300 cm −1 . They are presented in Supporting Information.